AB0022 Accumulation of circulating autoreactive naïve b cells reveal defects of early b cell tolerance checkpoints in patients with sjögren's syndrome. (23rd January 2014) - Corsiero, E.; Sutcliffe, N.; Wardemann, H.; Pitzalis, C.; Bombardieri, M.
Abstract : Background: Sjögren's syndrome (SS) is an autoimmune disease characterised by high affinity circulating autoantibodies and peripheral B cell disturbances with predominance of naïve and reduction of memory B cells. Objectives: The stage at which errors in B cell tolerance checkpoints accumulate in SS is unknown. Here we determined the frequency of self- and poly-reactive B cells in the circulating naïve compartment of SS patients. Methods: Single CD27-IgD+ B cells were sorted by FACS from peripheral blood of SS patients and healthy donors (HD). RNA was used to amplify Ig VH and VL genes and PCR products were cloned and expressed as recombinant monoclonal antibodies displaying identical specificity of the original B cells. Recombinant antibodies were tested towards different antigens to determine the frequency of autoreactive and polyreactive clones. Results: 66 recombinant antibodies were generated from naïve B cells of 4 SS patients and compared to 45 clones from 2 HD. Analysis of the VH and VL gene usage showed no significant differences between SS and HD. Conversely, we observed accumulation of circulating autoreactive naïve B cells in SS as demonstrated by increased reactivity towards Hep2 cells (43.1% SS vs 25% HD) and ENA (19.6% SS clones vs none). Among ENA+ clones, 6 displayed reactivity towards Ro/SSA and/or La/SSB. Conclusions: Here using an efficient strategy to express recombinant monoclonal antibodies from single B cells we demonstrated an elevated frequency of autoreactive naïve B cells in the circulation of SS patients supporting the existence of early defects in B cell tolerance checkpoints in SS. Disclosure of Interest: None Declared